Attendance at specialist hepatitis clinics and initiation of antiviral treatment among persons chronically infected with hepatitis C: examining the early impact of Scotland's Hepatitis C Action Plan. Issue 5 (2nd September 2013) - McDonald, S. A.; Hutchinson, S. J.; Innes, H. A.; Allen, S.; Bramley, P.; Bhattacharyya, D.; Carman, W.; Dillon, J. F.; Fox, R.; Fraser, A.; Goldberg, D. J.; Kennedy, N.; et al.
Summary Primary goals of the Hepatitis C Action Plan for Scotland Phase II (May 2008–March 2011) were to increase, among persons chronically infected with the hepatitis C (HCV) virus, attendance at specialist outpatient clinics and initiation on antiviral therapy. We evaluated progress towards these goals by comparing the odds, across time, of (a) first clinic attendance within 12 months of HCV diagnosis (n = 9747) and (b) initiation on antiviral treatment within 12 months of first attendance (n = 5736). Record linkage between the national HCV diagnosis (1996–2009) and HCV clinical (1996–2010) databases and logistic regression analyses were conducted for both outcomes. For outcome (a), 32% and 45% in the respective pre‐Phase II (before 1 May 2008) and Phase II periods attended a specialist clinic within 12 months of diagnosis; the odds of attendance within 12 months increased over time (OR = 1.05 per year, 95% CI: 1.04–1.07), but was not significantly greater for persons diagnosed with HCV in the Phase II era, compared with the pre‐Phase II era (OR = 1.1, 95% CI: 0.9–1.3), after adjustment for temporal trend. For outcome (b), 13% and 28% were initiated on treatment within 12 months of their first clinic attendance in the pre‐Phase II and Phase II periods, respectively. Higher odds of treatment initiation were associated with first clinic attendance in the Phase II (OR = 1.9, 95% CI: 1.5–2.4), compared with the pre‐Phase II era. Results were consistent with a positive impact of the Hepatitis C Action Plan on the treatment of chronically infected individuals, but further monitoring is required to confirm a sustained effect.